CHOLEDOCHODUODENOSTOMY: A VIABLE AND SAFE PROCEDURE IN PATIENTS WITH OBSTRUCTIVE JAUNDICE - Sultan, Syed; Ayub, Humayun; Ahmed, Rashid (Journal of Ayub Medical College Abbottabad, 1996)
A total of 2 7 patients with jaundice and/or other clinical, ultrasound or laboratory based diagnostic criteria of choledocholithiasis were included in this study. Perioperatively, all patients were well hydrated and received antibiotics perioperatively. Supraduodenal cholecystectomy was performed after cholecystectomy. Choledochoduodenostomy was performed using an interrupted stitch with catgut 2/0. There were no mortalities in our series. A few minor problems arose in two of our patients postoperatively. We suggest that Choledochoduodenostomy is a useful operation, technically easy, gives good results and should be practiced more often for both primary and secondary gall stones.